HAPS Gateway Link in the 5850-7075 MHz and Coexistence with Fixed Satellite Service - Ahmed, Marwah; Rahman, Tharek; Abdalla, Yousif (Společnost pro radioelektronické inženýrství, 2013)
Gateway link is essential to connect HAPS platform to terrestrial based networks. This crucial link is incorporated in HAPS fixed service spectrum allocation in considerably high frequencies, renders the link for more attenuations by atmospheric gases, and rain effects, especially when the regional climate is not favorable. However, under the agenda item 1.20 of World Radio Conference-2012 (WRC-12) new HAPS allocation in the 5850-7075 MHz band is proposed. Although, spectrum features are incomparably reliable, on the contrary, Fixed Satellite Service (FSS) uplink transmissions will have signal levels much higher than those in HAPS systems and have the potential for causing interference at the HAPS gateway receiver. In this article a key aspect of co-channel interference phenomena is investigated to facilitate optimum frequency sharing in the band in question. By proposing mitigation techniques and statistical method this generic prediction model enhances the capability of the HAPS spectrum sharing and provides flexibility in spectrum planning for different fixed services.
Keywords: Co-channel interference; minimum coupling loss; carrier-to-interference ratio; interference mitigation techniques; Monte-Carlo approach.